Thaixylomolins O–R: four new limonoids from the Trang mangrove, Xylocarpus moluccensis. Issue 89 (9th September 2016) - Dai, Yi-Guo; Li, Wan-Shan; Pedpradab, Patchara; Liu, Jun-Jun; Wu, Jun; Shen, Li
Abstract : Four new limonoids, including two novel phragmalin 8, 9, 12-orthoesters, were identified from the seeds of Thai mangrove, Xylocarpus moluccensis . Abstract : Two novel phragmalin 8, 9, 12-orthoesters, named thaixylomolins O–P (1–2 ), a 9, 10- seco mexicanolide with a unique trans -orientation of H5 and Me-19, named thaixylomolin Q (3 ), and the first secomahoganin-type 7-nor-limonoid with a 6-oxabicyclo[3.2.1]octan-3-one motif, named thaixylomolin R (4 ), were isolated from the seeds of a Thai mangrove, Xylocarpus moluccensis collected from the mangrove swamps of the Trang Province. The absolute configurations of these limonoids were unambiguously determined by HRESIMS, extensive NMR investigations, single-crystal X-ray diffraction analyses with Cu Kα radiation, and quantum-chemical electronic circular dichroism (ECD) calculations. Most notably, thaixylomolins O–P are unusual phragmalins with a 8, 9, 12-orthoacetate group reported for the second time. Thaixylomolin P exhibited antitumor activities against ovarian A2780 and A2780/T cells with an equal IC50 value of 37.5 μM.